Prevention and control of HIV/AIDS in China: lessons from the past three decades - Xu, Jun-Jie; Han, Meng-Jie; Jiang, Yong-Jun; Ding, Hai-Bo; Li, Xi; Han, Xiao-Xu; Lv, Fan; Chen, Qing-Feng; Zhang, Zi-Ning; Cui, Hua-Lu; Geng, Wen-Qing; Zhang, Jing; et al. (Chinese medical journal, 2021)
In the past 37 years, human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) has undergone various major transmission routes in China, with the world most complex co-circulating HIV-1 subtypes, even the prevalence is still low. In response to the first epidemic outbreak of HIV in injecting drug users and the second one by illegal commercial blood collection, China issued the Anti-Drug Law and launched the Blood Donation Act and nationwide nucleic acid testing, which has avoided 98,232 to 211,200 estimated infections and almost ended the blood product-related infection. China has been providing free antiretroviral therapy (ART) since 2003, which covered >80% of the identified patients and achieved a viral suppression rate of 91%. To bend the curve of increasing the disease burden of HIV and finally end the epidemic, China should consider constraining HIV spread through sexual transmission, narrowing the gaps in identifying HIV cases, and the long-term effectiveness and safety of ART in the future.